Melatonin inhibits ethylene biosynthesis by regulating MdERF1/MdERF3 pathway during apple fruit ripening - Chen Li; Qian Yu; Yanmin Du; Wenhui Wang; Yajing Si; Yuling Liang; Shijiao Lin; Guangxin Yang; Weiting Liu; Aide Wang; Yinglin Ji (Postharvest Biology and Technology, 2026)

Genome-wide characterization of the apple WOX family identifies MdWOX13 as a repressor of fruit ripening - Yinglin Ji; Shijiao Lin; Mingqian Wang; Yuling Liang; Meili Xin; Yanan Wang; Weiting Liu; Aide Wang; Bin Li (Postharvest Biology and Technology, 2026)

The role of growth differentiation factor 15 in the polarization and foaming of THP-1 macrophages induced by trans fatty acids from different sources - Jingyuan Lin; Weiting Fang; Yuan Yuan; Huijiao Shen; Xiaojing Shi; Guo Wang; Huzhong Li; Qifei Yang; Yang Yang; Xingcan Yang; Qibing Zeng; Haiqin Fang (Toxicology in Vitro, 2026)

Involvements of dicyclohexylcarbodiimide and adenosine diphosphate-mediated respiration and organic acid metabolisms in pulp acidification of Phomopsis longanae Chi-infected longan fruit - Weiting Bi; Yueying Sang; Wen Lin; Ruiling Zhuo; Mengshi Lin; Yihui Chen; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Food Chemistry, 2026)

Catalytic upgrading of clean biogas to synthesis gas via bi-reforming over bimetallic NiCo catalysts - Xinyu Huang; Weiting Lin; Zhichao Zhao; Pengyin Lu; Jun Xie; Jiawei Zhong; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Catalytic upgrading of biogas exclusively to metgas (CO-2H2) through the combined steam and dry reforming over Sm2O3 promoted robust Ni nano-catalysts supported on boron nitride nanosheets - Xinyu Huang; Weiting Lin; Pengyin Lu; Zhichao Zhao; Jiawei Zhong; Jun Xie; Yong Chen (Fuel, 2025)

Potential mechanism of impaired perceptual reasoning in children with obstructive sleep apnea syndrome: topological analysis of brain white matter network employing graph theory - Weiting Tan; Shaojun Zhang; Xiaoyu Wang; Guisen Lin; Wenhong Ye; Hongwu Zeng (Brain Imaging and Behavior, 2025)

Platelet-hitchhiking biomimetic nanoplatforms pry precisely tumor seed and growing soil for inhibiting tumor recurrence and metastasis - Yan Zhang; Weiting Sun; Guozheng Xing; Dunwan Zhu; Lin Mei; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

Corrosion-oriented self-healing coating based on ZnMg MOF for efficient corrosion protection of aluminum alloy via in-situ LDH film formation - Zhibin Chen; Jinke Wang; Lin Lu; Thee Chowwanonthapunya; Weiting Chen; Zongbao Li; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

An optically responsive cancer vaccine for inducing robust anti-tumor immunity by apoptotic body carrying nanoadjuvants - Limin Jin; Shupei Sheng; Yan Zhang; Weiting Sun; Lin Mei; Dunwan Zhu; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

Bi-reforming of model biogas into syngas over layered double hydroxides-derived bimetallic Ni-Ga catalysts - Wenyang Li; Guofeng Zhao; Xinyu Huang; Weiting Lin; Jun Xie; Jiawei Zhong (Fuel, 2024)

Can the phase of SNR oscillations in GNSS-IR be used to estimate sea-level height? - Zhenkui Wei; Chao Ren; Yueji Liang; Yintao Liu; Jieyu Liang; Anchao Yin; Weiting Yue; Xudong Zhang; Xiaoqi Lin (GPS Solutions, 2024)
In existing global navigation satellite system-interference reflectometry (GNSS-IR) research, only the frequency of signal-to-noise ratio (SNR) oscillations has been used to estimate sea-level height. However, the characteristic parameters of SNR oscillations are not isolated from each other, and a single feature cannot accurately and comprehensively capture the environmental changes of reflecting surface. Our simulation results show that for the nonlinear least squares (NLS), when there is a certain difference between the fitting frequency and the actual frequency of SNR oscillations, the deviation of the phase solution obtained is approximately linear with the frequency difference. Consequently, a linear phase correction GNSS-IR sea-level estimation method is constructed in this study. This method integrates the Lomb–Scargle periodogram (LSP) and NLS to process SNR oscillations, using the phase obtained from NLS to correct the retrieval error of LSP. Through processing SNR data from four sites for nearly half a year, we verified the stability of the relationship between phase and frequency-based retrieval error at different sites in continuous monitoring, and established the relationship model between the two. Then, utilizing the relationship model acquired at different sites, we estimated the sea-level variations for the next 6 months at each site through joint frequency and phase versus reflector height relationships. Experimental results show that the phases acquired from NLS can effectively correct the retrieval error of LSP. Compared with the traditional method using only frequency, the root mean square error and mean absolute error of the retrieval results obtained from the linear phase correction GNSS-IR sea-level estimation method based on LSP-NLS are both reduced by about 60%. This multi-feature fusion technique introduces a new perspective and technical approach for GNSS-IR sea-level estimations.

Improved Pb(II) removal by D001 resin with a facile nanoscale α-FeOOH modification - Bing Li; Zhiyi Deng; Xueying Lin; Weiting Chen; Ping Li; Jinhua Wu (Journal of Environmental Chemical Engineering, 2024)

A Fe-Ni-MOF-74@bamboo photothermal evaporator for efficient solar steam generation - Yiduo Chen; Dongxu Gu; Yujuan Zhao; Chaowei Zhang; Meiling Li; Qi Zhou; Yonghui Lin; Yaru Gong; Zhongmin Su; Weiting Yang (Desalination, 2024)

Integrated small RNA profiling and degradome analysis of Anthurium andraeanum cultivars with different-colored spathes - Fazhuang Lin; Shi-Peng Chen; Kuan-Hung Lin; Changming Chen; Fengqin Yao; Linshan Zhong; Weiting Chen; Yun-Wei Kuo (Journal of Plant Research, 2022)

Growth Promotion and Salt-Tolerance Improvement of Gerbera jamesonii by Root Colonization of Piriformospora indica - Weiting Chen; Fazhuang Lin; Kuan-Hung Lin; Changming Chen; Chaoshui Xia; Qiaoling Liao; Shi-Peng Chen; Yun-Wei Kuo (Journal of Plant Growth Regulation, 2022)